Implikasi Seni dalam Bermain Alat Musik Drum pada Anak Usia Dini - Rahmi, Aulia; Maemonah, M (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
In the artistic aspect, every child is a unique individual. Musical development in children involves an environment that encourages exploration, expression, and appreciation of art in the context of play. It involves the ability to explore and express oneself by using imagination in movement. The purpose of this study to explain the activities of playing musical instruments in early childhood. This research method is qualitative research with a case study approach as an analytical tool. Data was collected through direct observation, documentation, and literature review. This research was conducted at RA Ibnu Sina Palembang, with the subjects being class B students at that institution. Based on the results of the research, researchers found 3 indicators, namely children using drum musical instruments where the child was given a drum instrument first, correcting the position of the drum according to the child's comfort, the way the child expressed musical instruments by hitting the drum with a very happy face, and the teacher revealed the concept of the instrument. music by providing teaching in stages, one beat after another, so that every child can understand it.